Population survey of predatory insects in sugarcane in the municipality of União, Piauí state, Brazil, using light trap - Castelo Branco, Rommel Tito; Silva, Paulo Roberto Ramalho da; Portela, Gilson Lages Fortes; Padua, Luiz Evaldo de Moura; Santos, Ocimar Alencar Amorim dos (Científica, 2016)
Predatory insects are important to control agricultural pests. Knowledge of predators in sugarcane culture may allow for chemical control reduction. This study aimed to record predator entomofauna associated with sugarcane commercial cultivation in the municipality of União, State of Piaui. Insects were collected with a light trap, "Luiz de Queiroz" model, equipped with a F15 T8 BL lamp positioned 1.5 meters above ground in the geographical coordinates of 21 ° 22’ 30" S and 48 ° 13’ 0" W. The trap was turned on at 6 p.m. and turned off at 6.00 a.m., and sampling was conducted once a week. In a total of 52 collections, 83 predator species distributed in 07 orders, 17 families, and 45 genera were collected. Coleoptera and Hymenoptera orders were the most diverse, with 56 and 15 species, respectively. Selenophorus sp.1 (Coleoptera: Carabidae) was the species with the highest number of individuals among Coleoptera, and Linepithema humile (Mayr, 1868) (Hymenoptera: Fomicidae) was the species with trhe highest number among Hymenoptera.